2006
DOI: 10.4067/s0718-19572006000100012
|View full text |Cite
|
Sign up to set email alerts
|

Efecto del alga marina Sargassum spp. sobre las variables productivas y la concentración de colesterol en el camarón café, Farfantepenaeus californiensis (Holmes, 1900)

Abstract: 0,05) en cuanto a ganancia de peso, talla, tasa de supervivencia y factor de conversión alimenticia entre los dos tratamientos. La concentración de colesterol en los camarones alimentados con la dieta que contenía Sargassum fue estadísticamente (P<0,05) menor (77 mg/100 g) que en los alimentados con la dieta testigo (110 mg/100 g). Los resultados obtenidos muestran que 4% de harina Sargassum puede ser incorporada a los alimentos balanceados para camarón café, sin causar efectos negativos en sus parámetros prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Several works (Rivera et al, 2002;Gutiérrez-Leyva, 2006;Cruz-Suárez et al, 2009) evaluated the effect of including M. pyrifera meals in feeds for white shrimp Litopenaeus vannamei, with excellent results in terms of growth rate and survival. In the present study supplementation with polysaccharides extracts of seaweeds, M. pyrifera and U. pinnatifida showed in all treatments an acceptable survival for commercial crops (higher than 60%) (Clifford, 1994), with similar values than those obtained for other species of shrimp (Casas-Valdez et al, 2006;Cruz-Suárez et al, 2009). Studies reported that inclusion of brown algae in addition to improving growth, feed intake and feed texture, reduce dry matter loss and increase water absorption, proving to be an excellent binder for pelletized feeds (Cruz-Suárez et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
“…Several works (Rivera et al, 2002;Gutiérrez-Leyva, 2006;Cruz-Suárez et al, 2009) evaluated the effect of including M. pyrifera meals in feeds for white shrimp Litopenaeus vannamei, with excellent results in terms of growth rate and survival. In the present study supplementation with polysaccharides extracts of seaweeds, M. pyrifera and U. pinnatifida showed in all treatments an acceptable survival for commercial crops (higher than 60%) (Clifford, 1994), with similar values than those obtained for other species of shrimp (Casas-Valdez et al, 2006;Cruz-Suárez et al, 2009). Studies reported that inclusion of brown algae in addition to improving growth, feed intake and feed texture, reduce dry matter loss and increase water absorption, proving to be an excellent binder for pelletized feeds (Cruz-Suárez et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
“…As Sargassum presents their maximum abundance, bidder size and completed their reproductive and life cycle at the end of spring, this seaweed is commonly collected then to do different experiments, as in the present research. Results about the chemical composition of Sargassum, collected at the end of spring, show the following values, protein 6.1 to 7.7%, ash 31 to 38%, crude fiber 6.5 to 9.3%, and ether extract 0.34 to 1.8% (Carrillo et al 2002, Casas-Valdez et al 2006a, 2006b). The results obtained in this study (protein 7.7%, ash 33.3%, crude fiber 6.4% and ether extract 0.45%) are similar to the ones previously mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Some seaweeds have been suggested as a partial feed substitute ( Marinho-Soriano et al, 2007 ) for shrimp diet, and considered a good source of protein ( Da Silva & Barbosa, 2009 ), which represents the most expensive fraction of feed cost. In some cases, shrimp composition is modified when fed seaweeds, these changes may include lipid content and carotenoids ( Cruz-Suárez et al, 2010 ; Subhra Bikash, 2015 ), or total cholesterol ( Casas-Valdez et al, 2006 ). The optimal level of inclusion of seaweed meal in shrimp feed varies among seaweed species, but, in most cases, studies have found benefits when included not higher than 5% ( Cruz-Suárez et al, 2009 ; Rodríguez-González et al, 2014 ; Cárdenas et al, 2015 ; Yu et al, 2016 ; Schleder et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%